HUBUNGAN KOMITMEN ORGANISASI DAN OTONOMI PEKERJAAN MELALUI KUALITAS KARYAWAN DENGAN KINERJA KARYAWAN DI RSUD SYEKH YUSUF GOWA - Fitriyanti, Pipit; Masriadi, Masriadi; Hamzah, Wardiah (Ensiklopedia of Journal, 2025)
Abstract: The purpose of this study is to analyze the relationship between Organizational Commitment and Job Autonomy through Employee Quality and Employee Performance at Syekh Yusuf Regional General Hospital, Gowa. This study used an analytical observational design with a cross-sectional study. The study was conducted at Syekh Yusuf Regional General Hospital, Gowa Regency, in 2025. The population and sample size were 210 individuals using total sampling. Data analysis was performed using SPSS, and the collected data were analyzed using Partial Least Squares (PLS). The results of the study showed that Continuance (p 0.058), Independence (p 0.038), Discretion (p 0.000) had a positive influence on employee quality. On the other hand, Affective (p 0.058), Normative (p 0.118), and freedom (p 0.871) did not have a positive influence on employee quality at Syekh Yusuf Gowa Regional Hospital in 2025. The results also showed that Affective (p 0.000), Normative (p 0.045), Freedom (p 0.000), and discretion (p 0.000) had a positive influence on employee performance. On the other hand, Continuance (p 0.592), Independence (p 0.870) did not have a positive influence on employee performance. Furthermore, the research results also show that Affective (p 0.000), Continuance (p 0.000), Normative (p 0.000), Freedom (p 0.000), Independence (p 0.000), and Discretion (p 0.000) have a positive influence on employee performance through employee quality. Not all organizational commitment and job autonomy contribute to employee quality and performance. It is recommended that hospitals design strategies to improve employee quality and performance through a more effective organizational behavior approach.Keywords: Organizational Commitment, Job Autonomy, Employee Quality and Performance